What controls variation in carbon use efficiency among Amazonian tropical forests?. (10th October 2017) - Doughty, Christopher E.; Goldsmith, Gregory R.; Raab, Nicolas; Girardin, Cecile A. J.; Farfan‐Amezquita, Filio; Huaraca‐Huasco, Walter; Silva‐Espejo, Javier E.; Araujo‐Murakami, Alejandro; da Costa, Antonio C. L.; Rocha, Wanderley; Galbraith, David; Meir, Patrick; et al.
Abstract: Why do some forests produce biomass more efficiently than others? Variations in Carbon Use Efficiency (CUE: total Net Primary Production (NPP)/ Gross Primary Production (GPP)) may be due to changes in wood residence time (Biomass/NPPwood ), temperature, or soil nutrient status. We tested these hypotheses in 14, one ha plots across Amazonian and Andean forests where we measured most key components of net primary production (NPP: wood, fine roots, and leaves) and autotrophic respiration (Ra ; wood, rhizosphere, and leaf respiration). We found that lower fertility sites were less efficient at producing biomass and had higher rhizosphere respiration, indicating increased carbon allocation to belowground components. We then compared wood respiration to wood growth and rhizosphere respiration to fine root growth and found that forests with residence times <40 yrs had significantly lower maintenance respiration for both wood and fine roots than forests with residence times >40 yrs. A comparison of rhizosphere respiration to fine root growth showed that rhizosphere growth respiration was significantly greater at low fertility sites. Overall, we found that Amazonian forests produce biomass less efficiently in stands with residence times >40 yrs and in stands with lower fertility, but changes to long‐term mean annual temperatures do not impact CUE.